When x = 6, the expression becomes:
8 + 2(6)^2
= 8 + 2(36)
= 8 + 72
= 80
Therefore, when x = 6, 8 + 2x^2 equals 80.
evaluate the expression 8 + 2x^2 when x = 6
8 + 2x^2 = 8 + 2 (?)^2
7 answers
no answer the question mark
I apologize for the oversight. Let's calculate it correctly:
8 + 2(6)^2
= 8 + 2(36)
= 8 + 72
= 80
Therefore, when x = 6, 8 + 2x^2 equals 80.
8 + 2(6)^2
= 8 + 2(36)
= 8 + 72
= 80
Therefore, when x = 6, 8 + 2x^2 equals 80.
evaluate the expression 3a + 4b^3 - 5 when a = 6 and b = 2
3a + 4b3 - 5 = 3 (?) + 4 (?)^3 - 5
3a + 4b3 - 5 = 3 (?) + 4 (?)^3 - 5
When a = 6 and b = 2, the expression becomes:
3(6) + 4(2)^3 - 5
= 18 + 4(8) - 5
= 18 + 32 - 5
= 50 - 5
= 45
Therefore, when a = 6 and b = 2, the expression 3a + 4b^3 - 5 equals 45.
3(6) + 4(2)^3 - 5
= 18 + 4(8) - 5
= 18 + 32 - 5
= 50 - 5
= 45
Therefore, when a = 6 and b = 2, the expression 3a + 4b^3 - 5 equals 45.
evaluate the expression m + (3n - 5)^2 when m = 6 and n = 4
m + (3n - 5)^2 = ? + (3 x ? = 5)^2
m + (3n - 5)^2 = ? + (3 x ? = 5)^2
When m = 6 and n = 4, the expression becomes:
6 + (3(4) - 5)^2
= 6 + (12 - 5)^2
= 6 + (7)^2
= 6 + 49
= 55
Therefore, when m = 6 and n = 4, the expression m + (3n - 5)^2 equals 55.
6 + (3(4) - 5)^2
= 6 + (12 - 5)^2
= 6 + (7)^2
= 6 + 49
= 55
Therefore, when m = 6 and n = 4, the expression m + (3n - 5)^2 equals 55.